Organizational Culture Integration Initiation in Merger and Acquisition, Changing Work Culture and Employees’ Work Behavior - Gautam, Prakash Kumar (The Batuk, 2022)
In most of the mergers of financial institutions, the issue of human side i.e. justice, satisfaction and work behavior of employees are neglected. But, the success of the new organization after Merger and Acquisition (M&As), largely depends on how actively and innovatively their employees work in the changed working environment. Hence, the purpose of this study is to explore the organizations’ initiation for cultural integration in M&As process in Nepalese financial institutions. Further, it aims to examine how cultural integration initiation influence employees’ satisfaction and their work behavior. This research follows inductive-deductive approach as the variables or issues were induced primarily and the data were analyzed with quantitative techniques. 234 responses from employees working in new organizations after M&As, from the large and small organization of M&As, and managerial and non-managerial level were collected based on organizational justice and social identity theory. Descriptive statistics were used to analyze the data. The result of the study revealed poor cultural integration initiation from the top management during M&As. Feeling of workplace injustice is being increased which caused deviant work behavior of the employees. This study emphasizes on the urgent need of organizational justice and enhancing the social identity of the employees working in all the M&As organizations. The consequences of the poor cultural integration initiation associated to organizational justice and social identity add on comprehensive framework of these theories.